Korelasi Nilai Positif dan Negatif tentang Anak dan Gaya Pengasuhan Ibu di Kota Bandung - Ida Ayu Nyoman Kartikawati; Lie Fun Fun; Lisa Imelia Satyawan (Humanitas (Jurnal Psikologi), 2021)
This study aims to obtain a description of the correlation between positive and negative values ??of children and maternal parenting styles in Bandung. Targeted from the Value of Children theory, the presence of children has value in the family. Value that is someone believes in and determines behavior and goals. Mothers have a big social role in childcare, and bringing certain expectations from the care that is applied to children according to the values ??they have about children. Positive or negative values ??about children will relate and determine the behavior and goals of mothers which are reflected in their parenting style. The sample of this research is a mother who has at least 1 child in the city of Bandung, with a sampling cluter sampling technique. This research method uses correlational quantitative methods with data analysis techniques using simple regression Pearson Product Moment. The data collection technique was taken using a questionnaire. From the results of research on 310 mothers in the city of Bandung, it is found that positive values ??about children have a strong positive correlation with the authoritative parenting style of mothers in the city of Bandung, moderate positive correlation with authoritarian parenting styles and weakly correlated with permissive parenting styles. Negative values ??about children have a negative correlation with authoritarian parenting styles, have a positive and strong enough correlation with authoritarian and permissive parenting styles for mothers in Bandung. Keywords: value of children, positive and negative values about children, parenting style